The reproducibility and responsiveness of subjective assessment of upper limb associated reactions in people with acquired brain injury during walking. (February 2020) - Kahn, Michelle B; Clark, Ross A; Bower, Kelly J; Mentiplay, Benjamin F; Yong Hao, Pua; Olver, John; Williams, Gavin
Objective: The aim of this study is to determine inter-rater, test–retest and intra-rater reproducibility and responsiveness of subjective assessment of upper limb associated reactions in people with acquired brain injury using (1) the 'Qualifiers Scale' of the International Classification of Functioning, Disability and Health Framework, and (2) visually estimated elbow flexion angle during walking. Design: Observational study. Setting: A brain injury rehabilitation centre, Melbourne, Australia. Subjects: People with acquired brain injury and upper limb associated reactions and experienced neurological physiotherapists. Main measures: The Qualifiers Scale applied to individual upper limb joints and global associated reaction on a 5-point scale (0–4), a summed upper limb severity score and visually estimated elbow flexion angle. Results: A total of 42 people with acquired brain injury (mean age: 48.4 ± 16.5 years) were videoed walking at self-selected and fast speeds. A subset of 30 chronic brain injury participants (mean time post injury: 8.2 ± 9.3 years) were reassessed one week later for retest reproducibility. Three experienced neurological physiotherapists (mean experience: 22.7 ± 9.1 years) viewed these videos and subjectively rated the upper limb associated reactions. Strong-to-very strong test–retest, intra- and inter-rater reproducibility was found for elbow flexion angle (ICC > 0.86) and the Qualifiers Scale applied to global and individual upper limb joints (ICC > 0.60). Responsiveness of change from self-selected to fast walking speed (mean increase 0.46 m/s) was highest for elbow flexion angle (effect size = 0.83) and low-to-moderate for the Qualifiers Scale. Conclusion: Subjectively rated associated reactions during walking demonstrated strong reproducibility and moderate responsiveness to speed change. The Qualifiers Scale and elbow flexion angle can both subjectively quantify associated reactions during walking in a clinical setting.